An investigation into the characterisation of the spalling behaviour of Polycrystalline Diamond Compact(PDC) cutters under impact loading conditions - Williams, Justin Craig (Department of Mechanical Engineering, 2024)
An experimental investigation into the identification of the spalling mechanisms of polycrystalline diamond compact (PDC) cutters and the effect of stress wave shape on the degree of spalling was performed using the split-Hopkinson pressure bar (SHPB) apparatus. The PDC cutters were loaded under specific impact conditions and their reactions monitored and characterised. In order to isolate and identify the mechanism responsible for the spalling of the PDC cutters required them to be tested for compression waves, reflected tensile waves, contact stresses, resultant forces and normal forces. It was determined that the spalling phenomenon observed in PDC cutters was due to the application of excessive normal forces. The results obtained during the impact testing of the PDC cutters were of projected damage area and mass losses, which were converted to volume losses and average crack depth measurements. The loading conditions were characterised as the peak force, average force and impulse experienced by the PDC cutters which were then plotted as a function of each other as well as of the damage measurements. It was found that the degree of spalling is dependent on the amplitude of the applied stress wave and independent of the period. For this reason traditional drop testing methods cannot be used to describe the impact behaviour of PDC cutters and the SHPB apparatus therefore offers an alternative experimental technique.